GOOGLE CLASSROOM ASSISTED BLENDED LEARNING MODEL IN ISLAMIC RELIGIOUS EDUCATION CURRICULUM DEVELOPMENT COURSE - Rohmah, Atifatur; Rusydiyah, Evi Fatimatur (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2022)
This study aimed to determine the application of Google Classroom-based blended learning model as well as student responses to the learning model utilization. The research method used in this research was descriptive qualitative. While the type of research using field studies. It described the application of google classroom-based blended learning and student responses through observations and interviews. The data analysis used is in the form of data reduction, data presentation and then data conclusion. Based on the result of observation, it was found that the application of blended learning with implementation face-to-face learning as a whole is 74%, so that the face-to-face learning process in a pretty good category. While the implementation of online learning as a whole is 68%, so it is in a pretty good category. The percentage of student responses to the use of blended learning shows a figure of more than 61,51% and is in the high category. the use of blaended learning makes it easier for lecturers and students to carry out learning that can carry out face-to-face meetings in tertiary institutions.